Desenvolvimento de cerâmica vermelha utilizando rejeitos da construção civil - Silva, Juliana Emídia de Oliveira (2007)
The Industry of the Civil Construction has been one of the sectors that most contribute to the pollution of the environment, due to the great amount of residues generated by the construction, demolition and the extraction of raw material. As a way of minimizing the environmental impacts generated by this industry, some governmental organizations have elaborated laws and measures about the disposal of residues from the building construction (CONAMA - resolution 307). This work has as objective the reutilization of residues compound of sand, concrete, cement, red bricks and blocks of cement and mortar for the production of red ceramic, with the objective of minimizing costs and environmental impacts. The investigated samples contained 0% to 50% of residues in weight, and they were sintered at temperatures of 950°C, 1000°C, 1050°C, 1100°C and 1150°C. After the sinterization, the samples were submitted to tests of absorption of water, linear retraction, resistance to bending, apparent porosity, specific density, XRD and SEM. Satisfactory results were obtained in all studied compositions, with the possible incorporation of up to 50% of residues in ceramic mass without great losses in the mechanical strength, giving better results to the incorporation of 30% of residues in the fabrication of ceramic parts, such as roofing tiles, bricks masonry and pierced bricks